2015
DOI: 10.3390/rs70911639
|View full text |Cite
|
Sign up to set email alerts
|

Performance of High Resolution Satellite Rainfall Products over Data Scarce Parts of Eastern Ethiopia

Abstract: Accurate estimation of rainfall in mountainous areas is necessary for various water resource-related applications. Though rain gauges accurately measure rainfall, they are rarely found in mountainous regions and satellite rainfall data can be used as an alternative source over these regions. This study evaluated the performance of three high-resolution satellite rainfall products, the Tropical Rainfall Measuring Mission (TRMM 3B42), the Global Satellite Mapping of Precipitation (GSMaP_MVK+), and the Precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…The dekadal and monthly data were further classified to validate the satellite products at different elevations and for each of 12 months over the UBN basin, respectively. The double mass curve techniques and correlation coefficient analysis (similar to Gebere et al, 2015) confirmed the consistency and homogeneity of rain gauge observations, respectively.…”
Section: Methodssupporting
confidence: 54%
“…The dekadal and monthly data were further classified to validate the satellite products at different elevations and for each of 12 months over the UBN basin, respectively. The double mass curve techniques and correlation coefficient analysis (similar to Gebere et al, 2015) confirmed the consistency and homogeneity of rain gauge observations, respectively.…”
Section: Methodssupporting
confidence: 54%
“…The difference between the 3B42RT data and actual precipitation varied over the years. The 3B42RT observations were generally higher than the ground-based measurements before 2007, and the difference between the two was greater than 10 The difference between GWR-estimated and actual precipitation was lower that between the 3B42RT data and actual precipitation. The 3B42RT data overestimated precipitation before 2008, whereas the GWR model results were better correlated with the actual precipitation.…”
Section: Monthly Precipitation Distribution Estimationsmentioning
confidence: 71%
“…TMPA products, which combine remote sensing data from various passive microwave (PMW) and infrared (IR) sensors with gauge accumulation corrections based on the Global Precipitation Climatology Center (GPCC) monthly gauge analysis, aim to provide the global precipitation estimates from 50°N to 50°S at the TRMM-era. TMPA products have been widely examined and were proved to obtain a splendid success [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%